ISOLAMENTO E BIOPROSPECÇÃO DE FUNGOS TERMOFÍLICOS ISOLADOS DA FLORESTA OMBRÓFILA MISTA: PRODUÇÃO DE XILANASES POR Aspergillus fumigatus - MARMENTINI, JÉSSICA (2020)
The study of fungal biodiversity found in forest fragments is of great importance. Through knowledge of this biodiversity and the bioprospecting of biotechnological products, we seek to obtain subsidies to promote the conservation and valorisation of these remaining fragments. This work aimed to isolate thermophilous filamentous fungi from remnants of Araucaria Forest (AF), and to perform a bioprospecting for obtention of fungal strains xylanase producers. The objective was also to establish the optimal parameters for the production of these enzymes and to characterize them biochemically. In order to optimize production, the respective fungus was grown in Vogel liquid medium, in stationary condition at 45 ° C, for incubation periods and conditions specified by the Central Rotational Compound Design (DCCR) from planning 2 3 , where there was variation in cultivation time, pH of the medium and percentage of carbon source. In addition, the enzymes, in the non-purified form, were biochemically characterized in relation to the optimal temperature and pH of performance, thermal stability, stability against pH. The effect of adding ions and other substances to the reaction medium was also investigated. A total of 15 strains were isolated from AF soil and litter samples. Among these, the PJ10 strain distinghishes itself by the levels of xylanases produced when it grown in the presence of corn straw. The respective strain was molecularly characterized as belonging to the species Aspergillus fumigatus. Based on its growth potential under different temperatures, the respective strain was classified as thermotolerant. The highest levels of xilanase production were obtained when the fungus was grown for 72 hours, in the presence of 2% corn straw, at pH 9.0 and at 45 ° C, reaching 78,17 U/mL-1. Xylanases were more active at 65 ° C and at pH 6.0. They were not very stable at 60, 65 and 70 °C. Furthermore, the enzyme was stable in the pH range of 3.0 to 8.0, and it was activated by Mn2+ ,Cu2+, Mg2+ and β-mercaptoethanol and inhibited by Hg+ and SDS. From the results presented, it appears that the remaining fragments of AF exhibit great potential as sources of potentially new biological resources, such as the xylanase-producing thermophilic fungal strain described in the present investigation.